Impact of Personality Characteristics on Financial Inclusion of Women Employees in Pakistan: Moderating Impact of Digital Financial Literacy - Rizvi, Subeika; Azam Khan; Rabia Mumtaz (NUML International Journal of Business & Management, 2024)
The participation and inclusion of women are vital for the growth and progress of any economy. Literacy in finance is crucial for financial inclusion and facilitates, the usage of formal services in finance and products that enhance the economic opportunities for women. The aim of the study is to examine the effects of personality characteristics on financial inclusion among 250 female employees in the major metropolitan cities of Pakistan. Quantitative approach is employed in the study through a survey questionnaire to gather the data. The sampling technique was purposive which was used to select the women employees, and the PLS-SEM technique was used to analyze the data. The empirical findings of the current study show that financial attitude, behavior, and influence positively impact financial inclusion, which is moderated by digital financial literacy. This study adds value to the existing literature on the factors that affect financial literacy, especially in the context of women in Pakistan, and has important implications for policymakers in the financial sector. The paper proposes measures to enhance women’s engagement and inclusion in the financial sector and also provides future directions for research.